2011
DOI: 10.1158/1055-9965.epi-11-0545
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine, Carbon Monoxide, and Carcinogen Exposure after a Single Use of a Water Pipe

Abstract: Background Smoking tobacco preparations in a waterpipe (hookah) is widespread in many places of the world, including the US, where it is especially popular among young people. Many perceive waterpipe smoking to be less hazardous than cigarette smoking. We studied systemic absorption of nicotine, carbon monoxide, and carcinogens from one waterpipe smoking session. Methods Sixteen subjects smoked a waterpipe on a clinical research ward. Expired carbon monoxide and carboxyhemoglobin were measured, plasma sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 21 publications
4
99
1
3
Order By: Relevance
“…The limit of quantification (LOQ) was 42.0 ng nicotine/ml, and the coefficient of variance at 10 ng/ml was 9.2%. Nicotine concentrations below the LOQ were taken to be 1.4142 ng/ml (square root of the LOQ) as reported previously (Jacob et al, 2011).…”
Section: Nicotine Metabolites and Nmrmentioning
confidence: 99%
“…The limit of quantification (LOQ) was 42.0 ng nicotine/ml, and the coefficient of variance at 10 ng/ml was 9.2%. Nicotine concentrations below the LOQ were taken to be 1.4142 ng/ml (square root of the LOQ) as reported previously (Jacob et al, 2011).…”
Section: Nicotine Metabolites and Nmrmentioning
confidence: 99%
“…For example, a study of exposure to nicotine, carbon monoxide, and carcinogens in subjects who used waterpipes under controlled conditions found that users had significantly higher carbon monoxide levels than even cigarette smokers, which can pose potential health risks especially for people with cardiovascular and pulmonary diseases (Ref. 98). This study also found increased urinary levels of TSNAs and PAHs following waterpipe smoking (id.).…”
Section: Waterpipe Smokingmentioning
confidence: 99%
“…Hookah, a popular form of tobacco smoking, came into existence about four centuries ago where it was commonly used by people in Asia and Africa (Goodman, 1993;Shihadeh, 2003;World Health Organization, 2005). Other common names for hookah are waterpipe, shisha, hubble-bubble, nargileh and argileh (Chaaya et al, 2004;Maziak et al, 2004;Mohammad et al, 2008).…”
Section: Introductionmentioning
confidence: 99%